Generators shooting frequency of millimeter range of wave length with multiplication of frequency - A. V. Gusinsky; D. A. Kondrashov; A. S. Volynets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The structure of the construction of solid-state oscillating frequency oscillators in individual subranges of the millimeter wavelength range is given. In addition, the proposed principles for implementing the generation of signals in a wide range of frequency bands.